SOCIAL AND ECONOMICAL RESPONS OF FISHERMAN SOCIETY OF PONELO ISLAND TO THE DEVELOPMENT OF SARONDE ISLAND - Alamri, Annisa Rizqa (Universitas Gorontalo, 2018)
Human in their environment always give response to all things they recently accept. That response is also occurred in the community whose environment is developed to be a tourism attraction. The response is appear because of their need to utilize and improve their quality of life. The response of the community will affect the development of the tourismÂ attractions. The involvement of the private sector will cause response from the local community. The response appears from the community will show the communityâs acceptance of the development of tourism area. Thus the response of the fishermen community of Ponelo Kepulauan to the development of Saronde Island is interesting to be examined. The responses of the fishermen community seen in this research are social response and economic response that appears since Saronde Island is developed by the private sector.Â Qualitative method is used with case study approach to reveal the form and factor of social and economic response of the fishermen community towards the development of Saronde Island. This research is done in Ponelo Islands, North Gorontalo Regency, Gorontalo Province. The sources of the data used in this research are primary data and secondary data. The determination of informants are selected by using a purposive sampling technique. Data collection is done through observation, in-depth interviews and document studies. Data analysis is done with data reduction, presentation, and with draw the conclusion. To test the validity of the data obtained, this research used triangulation.Â Based on the findings in the field, researchers found that the social response of fishermen community of Ponelo Kepulauan to the development of Saronde Island tourism area includes a positive response and negative response. Positive response is the establishment of cooperation and adaptation of the fishermen community. Negative response is the indifferent society and the rejection of the fishermen community. The economic response of the fishermen community is the improvement of earnings after the development of Saronde Island. The response is influenced by several factors such as the income, perceptions, social and individual motives, and needs interests. All factor is working to encourage the emergence of social and economic response of fishermen communities of Ponelo Kepulauan to the development of Saronde Island.Â Â Â Key Words: Social Response, Economic Response, Fishermen Community